2023
DOI: 10.1021/acsestwater.3c00297
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Microplastics in Municipal Wastewater and Sludge Treatment Processes: A Review on Occurrence, Fate, and Effects

Jing Lu,
Zhi-Hui Dong,
Jia-Qi Zhou
et al.

Abstract: Biodegradable plastics have emerged as reliable alternatives to conventional plastics for alleviating global plastic pollution. However, biodegradable plastics could also rupture into microplastics and inevitably accumulate in wastewater treatment plants (WWTPs). The fate and effects of biodegradable microplastics (BMPs) in wastewater treatment and sludge disposal processes are of great concern but have not yet been reviewed. This review comprehensively expounded the occurrence, fate, and consequential effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 125 publications
0
0
0
Order By: Relevance
“…The popularity of biodegradable plastics might reduce plastic waste due to the advantage of biodegradability. However, evidence suggests that biodegradable plastics would result in more microplastics under natural conditions than conventional nonbiodegradable polymers. , For the first time, this work demonstrated that the BMPs that enter wastewater not only significantly weaken the denitrification performance regardless of whether there is sufficient carbon but also lead to more N 2 O emission than conventional NBMPs at a COD:N ratio of <4:1, because of intensified electron competition and regulated electron distribution, which has important implications for fully understanding the potential impacts of microplastics on wastewater treatment and greenhouse gas emission. Despite the lower resistance to decomposition, BMPs had more severe impacts on denitrifying sludge and N 2 O emission than did NBMPs.…”
Section: Environmental Implicationsmentioning
confidence: 83%
See 2 more Smart Citations
“…The popularity of biodegradable plastics might reduce plastic waste due to the advantage of biodegradability. However, evidence suggests that biodegradable plastics would result in more microplastics under natural conditions than conventional nonbiodegradable polymers. , For the first time, this work demonstrated that the BMPs that enter wastewater not only significantly weaken the denitrification performance regardless of whether there is sufficient carbon but also lead to more N 2 O emission than conventional NBMPs at a COD:N ratio of <4:1, because of intensified electron competition and regulated electron distribution, which has important implications for fully understanding the potential impacts of microplastics on wastewater treatment and greenhouse gas emission. Despite the lower resistance to decomposition, BMPs had more severe impacts on denitrifying sludge and N 2 O emission than did NBMPs.…”
Section: Environmental Implicationsmentioning
confidence: 83%
“…As for BMPs, there are different mechanisms responsible for the negative impacts, because, by contrast, the biocidal effect, ROS overproduction, and membrane damage were hardly detected. It is generally believed that NBMPs are extremely resistant to degradation in a biological wastewater treatment system because of the short solid retention time. , However, BMPs are more likely decomposed because these biodegradable polymers can be used as slow-release carbon sources during solid-phase denitrification . There might be some organic degradation intermediates of BMPs, providing a reasonable explanation for the significantly higher relative content of the fluorescent component [excitation and emission wavelengths of 251 nm (331 nm) and 415 nm, respectively] in the effluent (Figure S17).…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation